Studies on the helminth fauna of Japan. Part 9. Nematodes of fishes, I. - Yamaguti, S. (Japanese Journal of Zoology, 1935)
Yamaguti describes from Japanese fishes 37 species of nematodes belonging to 29 genera. Of these species 26 are new and 2 Capillaria remain undetermined. New forms included are as follows: Raphidascaris chirocentri n. sp. ; Contracaecum histiophori n. sp. ; C. pagrosomi n. sp. ; C. gracile n. sp. ; Paranisakis lophii n. sp.P. muraenesocis n. sp.; Philometra parasiluri n. sp. ; P. opsalichthydis n. sp. ; Philometroides n. g. for P. seriolae', Ichthyofilaria dasycotti n. g., n. sp. ; Sanguinofilaria lateolabracis n. g., n. sp. ; S. scomberomori n. sp. ; S. pinnicola n. sp. ; Clavinema parasiluri n. g., n. sp.; Anguillicolidae n. fam. for Anguillicola globiceps n. g., n. sp. ; Hedruris bryttosi n. sp. ; Heliconema anguillae n. sp. ; Rhabdochona zacconis n. sp. ; R. amago n. sp. ; R. girettae n. sp. ; R. gymnocranii n. sp. ; Spinitectus mogurndae n. sp. ; Procamallanus sigani n. sp. ; Cucullanus robustus n. sp. ; C. filiformis n. sp. and Cucullanellus pleuronectidis n. sp.